Ensure Longevity: An Extensive Analysis of Digital Preservation Techniques - Dubey, Payal (Journal of Advanced Research in Library and Information Science, 2024)
Digital preservation has become an essential endeavor in the modern era, as society increasingly relies on digital technologies for record-keeping, communication, and cultural heritage preservation. This review article provides an in-depth examination of the multifaceted landscape of digital preservation, encompassing strategies, challenges, and emerging trends. We delve into the imperative of preserving digital content amidst the ever-evolving technological landscape, highlighting its significance for safeguarding cultural heritage, enabling ongoing research, and ensuring organizational continuity. By exploring various preservation methodologies, including migration, emulation, and bit-level preservation, we uncover the intricate web of technical, organizational, and legal challenges that must be navigated. Furthermore, we spotlight recent advancements in artificial intelligence, blockchain technology, and community-driven initiatives that offer promising avenues for addressing these challenges. Through this comprehensive review, stakeholders gain insights into the complexities of digital preservation and are empowered to make informed decisions to safeguard invaluable digital assets for posterity.